Effects of Tai Chi Chuan on Inhibitory Control in Elderly Women: An fNIRS Study - Yang, Yuan; Chen, Tingting; Shao, Mingming; Yan, Shoufu; Yue, Guang H.; Jiang, Changhao (Frontiers in Human Neuroscience, 2020)
Background. Inhibitory control is a sub-ability of executive function and plays an important role in the entire cognitive process. However, declines in inhibitory control during aging significantly impair the quality of life of elderly people. Investigating methods to delay the decline of inhibitory control has become a focal point in current research. Tai Chi Chuan (TCC) is one effective method used to delay cognitive declines in older adults. However, the specific effects of TCC on inhibitory control and the mechanisms through which TCC may improve cognition in older adults have not been comprehensively investigated. Objective. The study explores possible neurological mechanisms related to the effects of TCC interventions on inhibitory control in older people using a functional near-infrared spectroscopy (fNIRS) technique and reaction times (RTs). Methods. A total of 26 healthy, elderly people who had not received TCC training completed all study procedures. The subjects were randomized to either the TCC group or the control group. Subjects in the TCC group were taught TCC by a certified instructor and trained for 8 weeks. The control group continued to perform general daily activities. The Flanker task was administered to every participant to evaluate inhibitory control pre- and post-intervention. While participants were performing the Flanker task, fNIRS data were collected. Results. Post-intervention, significant differences for incongruent flankers were found only for the TCC intervention group. Faster RTs were observed for the incongruent flankers in the TCC group than in the control group (p < .05). Analysis of the fNIRS data revealed an increase in Oxy-Hb in the prefrontal cortex during the incongruent flankers after the TCC exercise intervention. Conclusions. The TCC intervention significantly improved inhibitory control in older adults, suggesting that TCC is an effective, suitable exercise for improving executive function and neurological health in elderly people.